Statistical analysis of lake sediment geochemical data for understanding surface geological factors and processes: An example from Amazonian upland lakes, Brazil - Sahoo, Prafulla Kumar; Felix Guimaraes, Jose Tasso; Martins Souza-Filho, Pedro Walfir; Powell, Mike A.; Silva, Marcio Sousa da; Moraes, Aline Mamede; Alves, Ronnie; Leite, Alessandro Saba; Nascimento Junior, Wilson; Rodrigues, Tarcisio Magevski; Costa, Vladimir Eliodoro [UNESP]; Dall'Agnol, Roberto (Elsevier B.V., 2019)
Statistical evaluation applied to geochemical data of upland lake sediments and their catchment basins rocks from Serra dos Carajas was used to identify geochemical signatures associated with underlying processes, sediment provenances, and source-sink relationship. The lakes are Violao, Amendoim and Tres Irmas - TI1, TI2 and TI3. A centred log-ratio transformation (clr) was used prior to multivariate analyses in order to eliminate closure issues in compositional data. Due to the similarity between delta N-15 values and organic sources (mainly from C3 plants), the three lakes were clustered together. Violao Lake receives largest organic contribution from autochthonous sources, such as siliceous sponge spicules and algae, except for it shallower portion (WNW extension), which is more similar to TI2, having low delta N-15 values that are similar to the isotopic signature of upland swamps. The upper continental crust (UCC) normalization pattern shows that sediments are mainly enriched in Fe, P and Se, which is closely related to the catchment lithology. The distribution of elements in TI2 is significantly different from the other lakes, because it is dominated by organic carbon, while the other lakes are a mix of detritus and organic carbon. Factor Analysis (FA) using clr-transformed data distinguishes several geochemical assemblages in the sediments, with the major detritic groups being similar to catchment basin laterites: the Ti-Zr-Hf-Nb-Y-HREEs group corresponds to resistant minerals which remained stable during lateritization; the LREEs group reflects mobilization and reprecipitation by REE bearing minerals; and the Al-V-Cr-Sc association reflects metavolcanic rock. The Fe-P-Mo-As-Zn cluster in the sediments is attributed to Fe-oxyhydroxide precipitation, while TOC-SO3-Hg-Se group is controlled by organic matter. Principal Component Analysis (PCA) further indicates that detritic lake sediments are not directly derived from the parent rocks, but from weathered crusts, mainly ferruginous laterites and soils, which is consistent with their elements ratios.
Keywords: Multivariate statistics; Geochemical processes; Upland lakes; Sediments; Amazonia; Serra dos Carajas